Redesign identification criteria for major hazard installation in Malaysia - Syed Muhammad, Syed Malek; Harun, Razif (Wiley, 2022)
Malaysia adopted the GHS through the CLASS Regulations of 2013. This new approach for chemical classification is inconsistent with the CIMAH Regulations of 1996 and has introduced new hazard categories, which are not included in the current major hazard identification criteria. For identifying MHI in Malaysia, the chemicals need to be reclassified. Therefore, this study aims to propose the indicative criteria for major hazard installation that are aligned with CLASS in order to simplify the process. The newly listed chemical threshold quantity, focusing on the acute toxicity group, was also identified. The steps involved include comparing major hazard legislation in the selected country, matching the criteria of CIMAH and CLASS, and reclassifying chemicals in Schedule Two of CIMAH. For estimation of TQ for nitric acid, dispersion modeling was selected. A guide for selecting suitable parameters was developed, ALOHA software was used to simulate the model, and the estimation result for nitric acid was 15.5 tonnes. This study provides the opportunity to improve CIMAH by applying CLASS hazard categories to identify major hazard installation. The guide to estimate TQ could be used for other acute toxicity chemicals as an option for regulators to negotiate and decide the TQ in CIMAH.